Sustained S-IgG and S-IgA antibodies to Moderna’s mRNA-1273 vaccine in a Sub-Saharan African cohort suggests need for booster timing reconsiderations - Serwanga, Jennifer; Ankunda, Violet; Katende, Joseph Ssebwana; Baine, Claire; Oluka, Gerald Kevin; Odoch, Geoffrey; Nantambi, Hellen; Mugaba, Susan; Namuyanja, Angella; Ssali, Ivan; Ejou, Peter; Kato, Laban; et al. (Frontiers in Immunology, 2024)
This study sought to elucidate the long-term antibody responses to the Moderna mRNA-1273 COVID-19 vaccine within a Ugandan cohort, aiming to contribute to the sparse data on m-RNA vaccine immunogenicity in Sub-Saharan Africa. We tracked the development and persistence of the elicited antibodies in 19 participants aged 18 to 67, who received two doses of the mRNA-1273 vaccine. A validated enzyme-linked immunosorbent assay (ELISA) was used to quantify SARS-CoV-2-specific IgG, IgM, and IgA antibodies against the spike (S) and nucleoproteins (N). The study's temporal scope extended from the baseline to one year, capturing immediate and long-term immune responses.Statistical analyses were performed using the Wilcoxon test to evaluate changes in antibody levels across predetermined intervals with the Hochberg correction for multiple comparisons. Our results showed a significant initial rise in spike-directed IgG (S-IgG) and spike-directed IgA (S-IgA) levels, which remained elevated for the duration of the study. The S-IgG concentrations peaked 14 days after -boosting, while spike-directed IgM (S-IgM) levels were transient, aligning with their early response role. Notably, postbooster antibody concentrations did not significantly change. Prior S-IgG status influenced the post-priming S-IgA dynamics, with baseline S-IgG positive individuals maintaining higher S-IgA responses, a difference that did not reach statistical difference post-boost. Three instances of breakthrough infections: two among participants who exhibited baseline seropositivity for S-IgG, and one in a participant initially seronegative for S-IgG. . In conclusion, the mRNA-1273 vaccine elicited robust and persistent S-IgG and S-IgA antibody responses, particularly after the first dose, indicating potential for long-term immunity. Prior viral exposure enhances post-vaccination S-IgA responses compared to naive individuals, which aligned with the prior-naïve, post-boost. The stable antibody levels observed post-booster dose, remaining high over an extended period, with no significant secondary rise, and no difference by baseline exposure, suggest that initial vaccination may sufficiently prime the immune system for prolonged protection in this population, allowing for potential to delay booster schedules as antibody responses remained high at the time of boosting. This finding calls for a reassessment of the booster dose scheduling in this demographic.